Did Covid-19 Cost Trump the Election? - James Lake; Jun Nie (Center for Economic Studies and Ifo Institute (CESifo), 2021)
A common narrative is that COVID-19 cost Trump re-election. We do not find supporting evidence; if anything, the pandemic helped Trump. However, we find substantial evidence that voters abandoned Trump in counties with large increases in health insurance coverage since the Affordable Care Act, presumably fearing the roll-back of such expansion. Absent this effect, our estimates imply Trump would been on the precipice of re-election by winning Georgia, Arizona, Nevada, and only losing Wisconsin by a few thousand votes. Finally, while US trade war tariffs boosted Trump's support, foreign trade war tariffs and US agricultural subsidies had little effect.
Keywords: D72; F13; F14; I18; 330; 2020 US Presidential election; Covid-19; Affordable Care Act; health insurance coverage; trade war; political economy; trade policy